Possibility of Increasing Yield Potential of Rice By Reducing Panicle Height in the Canopy. I. Effects of Panicles on Light Interception and Canopy Photosynthesis - Setter, T.L.; Conocono, EA; Egdane, JA; Kropff, M.J. (Commonwealth Scientific and Industrial Research Organisation, 1995)
A new rice (Oryza sativa L.) plant type is proposed which is aimed at greater light interception by the leaves during grain filling and reduced susceptibility to lodging. This plant type is based on lowering panicle height in the canopy so that leaves are able to intercept more radiation. Panicle height of four cultivars with high yield potential ranged from 80 to 95% of canopy height at 14 days after flowering (DAF). Harvested panicle area index of two of these which were two tropical cultivars amounted to 0.45-0.57 m2 m-2, while the leaves above the panicles intercepted only 4-12% incident radiation at midday in these cultivars at 14 DAF. The potential impact of lowering panicle height in the canopy on canopy photosynthesis was evaluated by panicle removal. When panicles were removed, the irradiance at the bottom of the panicle layer of the canopy increased from 52 to 80%. At 11 DAF, net canopy photosynthesis of two cultivars similarly increased by 42-52% following removal of panicles. Increases in canopy photosynthesis were mainly due to increased light interception by leaves within the canopy since there were little or no changes in canopy dark respiration or in net leaf photosynthesis rates at the same irradiance following panicle removal. Optimum panicle height in the canopy and the effect of different panicle area index is further examined using a physiological model for light competition, INTERCOM. Reduced panicle height in the canopy is discussed in terms of considerations for and impacts of lowering panicle height in the canopy on canopy photosynthesis and yield of rice.